EDUCATION RELATIONSHIP AND PARENTS ' INCOME WITH THE INCIDENCE OF CHILD MARRIAGE AT THE OFFICE OF RELIGIOUS AFFAIRS IN WONOSARI DISTRICT MALANG - Denok Pitra Rhena (Universitas Airlangga, 2020)
The phenomenon of child marriage still causes controversy in the society. According to the child protection law, someone who is less than 18 years old has not been allowed to marry because he / she is considered underage. The marriage law states that it is legal for women who are married at the age of 16 as long as they get permission from their parents. The role of parents is very important in their child's marriage decisions. Parents are the key in an efort to reduce the prevalence of child age marriages. The study design used an observational design with a casecontrol design analytical approach.This research aims to analyze the relationship between parental factors and the incidence of child marriage in Wonosari, Malang.This research was conducted in Wonosari, Malang with samples that included 44 people as cases and 44 people as controls. The method of sampling was a simple random sampling technique. Variables in this research include the child marriage, the family income and the educational background of the head of the family. Data analysis was performed using the chi square test (α=0,05). The results shows that there is a relationship between educational background (p = 0.000) and family income (p = 0.000) with the incidence of child marriage. In conclusion, the educational background of the head of the family and family income are related to the incidence of child marriage. There should be an agreement between the marriage law and the child protection law regarding the marriage age limit that is in accordance with the physical, mental, and reproductive health of the child.Keywords: child marriage, educational background, family income, parent's role, rural area